Effectiveness of Forest and Land Fire Mitigation in South Sumatra: An Analytical Approach using Analytical Hierarchy Process and Importance Performance Analysis - Novitasari; Monik, Della Tiara (Jurnal Sylva Lestari, 2025)
In Indonesia, forest and land fires remain a major environmental issue. In 2022, South Sumatra recorded 51,972 ha of burned land, accounting for 25% of the nationwide total. These incidents resulted in severe air pollution, health risks, economic losses, and environmental degradation, underscoring the urgency of mitigation. This research employs a mixed-methods approach, combining Kernel density analysis, the Analytical Hierarchy Process (AHP), and Importance Performance Analysis (IPA) to assess fire mitigation in South Sumatra. The results indicate that Ogan Komering Ilir, Ogan Ilir, Penukal Abab Lematang Ilir, Musi Rawas, and Prabumulih are the most fire-prone districts. Human activity was the dominant factor (0.80), particularly land clearing. The AHP analysis indicated that prevention is the highest priority (0.77), reflecting its cost-effectiveness and sustainability compared to suppression. The IPA emphasized three preventive measures as most effective: hotspot monitoring, water reservoirs, and canal blocks. Hotspot monitoring enables early detection and rapid response, reservoirs maintain soil moisture to reduce fire risk, and canal blocks restore peatland hydrology to limit large-scale burning. Suppression (0.14) ranked second, highlighting its necessity for a rapid response despite its lower effectiveness and higher cost. Management (0.09), although the lowest weighted, remains important for land rehabilitation and ecosystem restoration, despite requiring time and resources. Overall, these findings demonstrate that effective mitigation depends on prioritizing prevention through technology-driven monitoring and water management infrastructure, supported by regulatory enforcement. Suppression and management serve as complementary strategies to strengthen ecosystem resilience. This research provides a foundation for integrating fire prevention into governance frameworks, supporting sustainable forest management in South Sumatra and other fire-prone districts. Keywords: Analytical Hierarchy Process, forest and land fires, Importance Performance Analysis, mitigation, South Sumatra